La construcción discursiva de la unidad lingüística en el Congreso Literario Hispanoamericano (Madrid, 1892) - Rizzo, María Florencia (2011)
In the context of the crisis in which Spain is involved towards the end of the 19th century and the processes of conformation and consolidation of the national States in Latin America, takes place in Madrid in 1892 a political-linguistic singular event: the Literary Spanish-American Congress, organized in order to celebrate the 4th Centenary of the Discovery of America. The present work proposes to analyze the political and linguistic orientations which go through the meeting. In that sense, we have shaped a corpus composed by the programme of topics and a selection of the exposed memories. To our mind, the discourses of the Congress are part of a matrix with hispanist orientation which generates an effect of homogeneity, of discursive unity. Nevertheless, inside this matrix there are delimited tensions, positionings, which are orientated to a pole of pronounced hispanist tendency or, on the contrary, more americanist.